Performing Modernism A Jewish Avant-Garde in Bucharest - Chiriac, Alexandra (De Gruyter, 2022)
This volume constitutes the first in-depth study of modernism in design and performance in interwar Romania, covering the period 1924 to 1934. It focuses on Jewish avant-garde artists and cultural producers, as well as design educators, arts patrons, and women entrepreneurs. Based on extensive research in Romania, Latvia, Germany, and the United States, it highlights the transnational impact of Jewish cultural production and its contribution to avant-garde movements across Europe and further afield. It shows how Bucharest was connected to places such as Berlin, Paris, Riga and Chicago through modern design and experimental Yiddish theatre, and argues that the Schule Reimann was more influential in Romania than the Bauhaus. Drawing on scholarship from the fields of performance studies, design history, and art history, this volume makes a valuable new contribution to histories of modernism and avant-garde.